2010
DOI: 10.1007/s00227-010-1394-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of climate warming on the recruitment of an economically and ecologically important species, the European lobster (Homarus gammarus) at Helgoland, North Sea

Abstract: A laboratory-based study was performed to assess the impact of climate warming on the recruitment of the endangered population of the European lobster (Homarus gammarus) at Helgoland (North Sea, German Bight). Egg-bearing females collected in situ just after spawning in late summer were subjected to various seasonal temperature regimes. Regimes with elevated temperatures (mild winters) resulted in a strong seasonal forward shift of larval hatching. Hatching took place at significantly lower temperatures than u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…However, the timing of moulting varied by few weeks only depending on different seasonal temperature regimes (Templeman 1940). In another study, no moulting occurred at or below 108C in lobster larvae (Schmalenbach & Franke 2010), and Aiken & Waddy (1976) reported that in lobsters held below 68C the moult induction was blocked.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the timing of moulting varied by few weeks only depending on different seasonal temperature regimes (Templeman 1940). In another study, no moulting occurred at or below 108C in lobster larvae (Schmalenbach & Franke 2010), and Aiken & Waddy (1976) reported that in lobsters held below 68C the moult induction was blocked.…”
Section: Discussionmentioning
confidence: 94%
“…Temperature thresholds appear to be associated with several stages of the lobster life cycle at Helgoland. The timing of embryogenesis and larval hatch was strongly dependent on late winter and spring temperatures (Schmalenbach & Franke 2010). In juvenile lobsters first moults and enhanced locomotory activity started when a threshold between 12 and 158C was passed independent of year class, which means also independent of size, underlining the importance of the temperature factor.…”
Section: Activity Of Juvenile European Lobsters 23mentioning
confidence: 97%
See 1 more Smart Citation
“…This approach was used to determine the duration of the larval stages at the given experimental conditions (Table 1). Additional data about the duration of larval development were provided by Schmalenbach and Fanke (2010).…”
Section: Maintenance and Rearing Of Lobster Larvaementioning
confidence: 99%
“…Within about 14 days, the larvae pass three zoea stages and molt into the first juvenile stage (Charmantier et al 1991;Schmalenbach and Fanke 2010). Similar to the adults, the larvae have to reduce and re-organize their muscles as well as the connective tissue.…”
Section: Introductionmentioning
confidence: 99%